To Reoffend or Not to Reoffend? An Investigation of Recidivism Among Individuals With Sexual Offense Histories and Psychopathy. (February 2021) - Leung, Pauline C.; Looman, Jan; Abracen, Jeffrey
Although psychopathy is a well-established risk factor for recidivism among those who have committed sexual offenses, there are nonetheless some individuals with sexual offense histories who are high in psychopathy but do not recidivate. This population—nonrecidivating psychopathic sex offenders (NRP-SOs)—was the focus of the current investigation. Data from 111 individuals with sexual offense histories who received a Hare Psychopathy Checklist–Revised (PCL-R) rating of at least 25 (suggesting the presence of psychopathy) were analyzed. With recidivism operationalized as the accrual of any new serious—that is, violent or sexual—charges, 39 recidivated (RP-SOs), whereas 72 did not (NRP-SOs). A logistic regression was conducted to assess whether NRP-SOs could be differentiated from RP-SOs. Being older at the time of release, a lesser criminal history, and being married predicted nonrecidivism. PCL-R factor scores and sexual deviance were not predictive. These findings highlight the heterogeneity that exists, even among those high in psychopathy.